2019
DOI: 10.18331/brj2019.6.2.3
|View full text |Cite
|
Sign up to set email alerts
|

A review on biomass: importance, chemistry, classification, and conversion

Abstract: HIGHLIGHTS Overview of biomass sources and related chemical composition are presented. Biomass conversion technologies and final products are reviewed and discussed. Economic and environmental analysis of biomassderived energy production was presented. Challenges for further expanssion of biomassderived energy production are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
250
0
26

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 654 publications
(279 citation statements)
references
References 59 publications
3
250
0
26
Order By: Relevance
“…Ginger lily grows easily in mild climates [8] and might even be harvested several times per year. They are similar to all other NBCF in many aspects but reveal marked differences in the relative amounts of their main components (cellulose, lignin, and hemicellulose) [7,9]. Ginger lily fibers contain by weight~6% hemicelluloses,~12% lignin [7,9], and high cellulose content of~79%, while cellulose content of sisal, jute, and hemp fibers has been found to be 65%, 61-71%, and 68%, respectively [7].…”
Section: Introductionmentioning
confidence: 76%
“…Ginger lily grows easily in mild climates [8] and might even be harvested several times per year. They are similar to all other NBCF in many aspects but reveal marked differences in the relative amounts of their main components (cellulose, lignin, and hemicellulose) [7,9]. Ginger lily fibers contain by weight~6% hemicelluloses,~12% lignin [7,9], and high cellulose content of~79%, while cellulose content of sisal, jute, and hemp fibers has been found to be 65%, 61-71%, and 68%, respectively [7].…”
Section: Introductionmentioning
confidence: 76%
“…However, it is lignocellulosic in nature (35.89% lignin) and thus rich in energy content [28]. Lignin content of biomass can be used for heat and power production [29,30], and was confirmed to contribute to bulk density and durability of briquettes [31]. Ultimate and proximate analysis including the calorific value of OPT have shown that it has the potential to serve as a good feedstock for biofuel production [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of biomass into biofuels or bioenergy can be performed through several processes, such as mechanical (chopping, palletization, and briquetting), thermochemical (combustion, gasification, pyrolysis, and torrefaction) and biochemical (fermentation and anaerobic digestion) conversion processes (Demirbaş, 2001;McKendry, 2002;Bridgwater, 2012;Tanger et al, 2013;Ranisau et al, 2016;Yelmen et al, 2016;Tursi, 2019). The criteria for choosing the most favorable biomass conversion process from these options are various including the type of biomass (solid, liquid or mixed sample), the biomass properties and characteristics, the desired energy product and utilization, conversion costs, as well as storage and transportation considerations.…”
Section: Introductionmentioning
confidence: 99%